Characterizing the structural properties and porosity of mid-urethral slings with varied manufacturing techniques - Knight, Katrina; Meyn, Leslie; Moalli, Pamela (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionImplantation of mid-urethral slings (MUSs) is a safe and effective approach for the surgical repair of stress urinary incontinence. However, concerns regarding the deformability of the prototype MUS, mechanical cut Gynecare TVT prompted manufacturers to use techniques like laser cutting, heat-sealing, and the inclusion of an interwoven stabilizing suture to decrease deformation with loading. We hypothesized that a laser cut or heat-sealed MUS would be stiffer but deform less, and experience less permanent elongation as compared to a mechanical cut MUS. Additionally, the inclusion of a stabilizing suture would minimize the loss of porosity.MethodsUniaxial tensile testing to failure and cyclic loading was performed to analyze the structural properties and permanent elongation, respectively, of commercially available MUSs Gynecare TVT (mechanical cut), Gynecare TVT Exact (laser cut), ArcTV (laser cut, with and without the stabilizing suture), and Desara Blue (heat-sealed). A custom Mathematica code was used to quantify the porosity of the MUSs following sequential uniaxial loading from 0 N to 10 N.ResultsDesara Blue was significantly stiffer (p-values < 0.05), elongated less at failure (p = 0.002), and experienced less permanent elongation in response to cyclic loading (p-values = 0.001) relative to Gynecare TVT. Similarly, permanent elongation was significantly less (p-values = 0.004) and the stiffness was higher (p = 0.004) for Gynecare TVT Exact as compared to Gynecare TVT. Very little differences in stiffness and no differences in relative elongation at failure nor permanent elongation were observed between ArcTV (without the interwoven suture) and Gynecare TVT (p-values > 0.05). The porosity of all MUSs significantly decreased with loading (p-values < 0.001); except for ArcTV with the stabilizing suture which showed the least amount of deformation (i.e., percent change in porosity decreasing by only 14%, p < 0.001, at 10 N).DiscussionOverall, heat-sealing decreased deformability at the cost of markedly increasing device stiffness to a point which likely outweighs benefits, and risks increased complications. Laser cutting had different effects on the behavior of TVT Exact and ArcTV suggesting manufacturer technical differences, but overall reduced deformation without a substantial impact on stiffness. An interwoven stabilizing suture minimized the loss of porosity which translates clinically to less deformation and mechanistically to reduced mesh complications.